Biological drugs in the treatment of atopic dermatitis – recommendations of the Polish Dermatological Society, the Polish Society of Allergology, the Polish Pediatric Society and the Polish Society of Family Medicine - Roman Nowicki; Magdalena Trzeciak; Lidia Rudnicka; Jacek Szepietowski; Marek Kulus; Maciej Kupczyk; Agnieszka Mastalerz-Migas; Jaroslaw Peregud-Pogorzelski; Karina Jahnz-Różyk; Joanna Narbutt; Magdalena Czarnecka-Operacz; Rafał Czajkowski; et al. (Przegląd Dermatologiczny, 2020)
The basis for development of atopic dermatitis are genetic, immunological and microbiological abnormalities as well as epidermal barrier defects. The course of the disease includes periodic exacerbations and remissions. Its development and course are influenced by numerous environmental and individual factors. In recent decades, in industrialized countries, a threefold increase in the incidence of atopic dermatitis was observed. There also is an increasing number of cases resistant to topical treatment. Effective treatment of atopic dermatitis should provide control of clinical symptoms, prevent exacerbations and improve the quality of life of patients. The multifactorial etiopathogenesis and various endotypes and phenotypes of the disease justify the tendency to optimize and personalize the therapy. Currently, we recommend the use of dupilumab for the treatment of patients from 12 years of age with moderate and severe atopic dermatitis, who do not respond to topical treatment.